Kratom as a potential substance use disorder harm reduction agent - Green, MeShell; Vadiei, Nina; Veltri, Charles A.; Grundmann, Oliver; Evoy, Kirk E. (Frontiers in Public Health, 2024)
Substance use disorders contribute to considerable U.S. morbidity and mortality. While effective pharmacotherapy options are available to treat opioid and alcohol use disorders, for a variety of reasons, many patients lack access to treatment or may be reluctant to seek care due to concerns such as perceived stigma or a current lack of desire to completely curtail their substance use. Furthermore, treatment options are limited for patients with stimulant or polysubstance use disorders. Thus, there is considerable need to expand the substance use disorder harm reduction armamentarium. Kratom (Mitragyna speciosa Korth.) is an herbal substance that can produce both opioid and stimulant-like effects, and its use in the US is growing. Though there are concerns regarding adverse effects, dependence risk, and limited regulation of its manufacturing and sale, the pharmacology of kratom and early preclinical studies suggest a potential role as a harm reduction agent for various substance use disorders, and it has historically been used in Southeast Asia for such purposes. The goal of this review is to describe kratom’s history of use, pharmacology, and early pre-clinical and observational research regarding its therapeutic potential in opioid use disorder, as well as alcohol, stimulant, and polysubstance use disorders, while also highlighting current concerns around its use, existing gaps in the literature, and directions for future research.